Rhyzopertha dominica Fabricius (Coleoptera: Bostrichidae): Growth and Development on Six Maize (Zea mays L.) Varieties - Ludji Pantja Astuti; Surya Setyawan; Tita Widjayanti (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
The research aimed to evaluate the Rhyzoperta dominica growth and development on six maize varieties. The No-choice method was adopted to evaluate the R. dominica life cylce from February to September 2018. Based on the result, the R. dominica growth and development were appropriate to be examined by the number of eggs, larvae, pupae, and F1 progenies and the percentage of weight loss rather than using the development time, the stage of development time, the median development time, the growth index of larvae, the potential of biotic, and susceptibility index. The development and the median development time were positively correlated with number of eggs, larvae, pupae, and F1 progenies. The R. dominica growth and development were faster on maize ‘ROK’ variety than other maize varieties. The highest number of eggs, larvae, pupae, and F1 progenies and the percentage of weight loss were detected on ‘ROK’ variety. On the other hand, the lowest growth and the longest development were observed on ‘Anoman’ variety. The variation of the R. dominica growth and development was due to the variation of the physical and biochemical characteristics of maize varieties.